Stricture of the descending colon due to schistosomiasis. Issue 611 (September 1976) - Wright, S. G.; Renton, Peter; Swarbrick, E. T.
Abstract : An example of a localized non-fibrous stricture of the colon due to Schistosoma mansoni infection is reported. The radiological and colonoscopic features are described. After treatment of the infection with niridazole, the stricture resolved completely. The pathogenesis of bowel lesions in schistosomiasis is briefly discussed.